Peritonitis Generalisata Et Causa Perforasi Gaster pada Wanita 71 Tahun dengan TB Paru Milier dan Gagal Ginjal Akut : Laporan Kasus - Angtoni, Miranda; Sucinta, Ardianto (Syntax Corporation, 2025)
Gastric perforation is a severe condition caused by the destruction of the stomach wall, leading to communication between the gastric lumen and the peritoneal cavity. The primary causes of gastric perforation include peptic ulcer disease, trauma, or malignancy. Peritonitis resulting from gastric perforation often leads to fatal complications, especially in patients with comorbidities such as miliary pulmonary tuberculosis and acute kidney failure. This case report presents a 71-year-old female with generalized peritonitis due to gastric perforation, accompanied by miliary pulmonary tuberculosis and acute kidney failure. The diagnosis was established based on clinical manifestations, laboratory findings, and radiological imaging showing pneumoperitoneum and a reticulonodular pattern in the lungs. The patient underwent emergency exploratory laparotomy with perforation repair using an omental patch. Despite the interventions, the patient's condition deteriorated postoperatively, ultimately leading to death. This case highlights the importance of early detection and aggressive management in high-risk patients to improve prognosis.